Quantifying Post-Eruption Vegetation Recovery on Mount Semeru Using UAV Time-Series Imagery - Romadoni, Ludwick Satria; Husamah, H.; Rahardjanto, Abdulkadir; Permana, Tutut Indria; Shukri, Ahmad Adnan Mohd (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
The December 2021 eruption of Mount Semeru caused massive ecological damage, initiating primary succession across landscapes buried by volcanic material. While satellite monitoring provides macro-scale trends, the micro-scale spatiotemporal dynamics and specific topographic drivers of early recovery remain poorly understood. This study quantifies the rate of vegetation recovery and statistically evaluates its micro-topographic constraints. We conducted a time-series analysis using ultra-high-resolution (2.7 cm/pixel) Unmanned Aerial Vehicle (UAV) RGB imagery acquired in 2022, 2023, and 2025 across a 127.08-hectare Area of Interest within Volcanic Hazard Zone III. Vegetation cover was extracted using the Excess Green (ExG) index with dynamic Otsu thresholding, validated by rigorous accuracy assessments (Overall Accuracy: 89%–95%). A 3-bit spatial coding logic tracked pixel-level successional trajectories, while topographic controls were evaluated using a non-parametric Mann-Whitney U test based on spatial random sampling. The results revealed a net vegetation recovery rate of +1.88 hectares/year, forming concentrated succession islands. Crucially, statistical analysis confirmed that micro-topographic slope acts as the primary abiotic control (p < 0.001); pioneer vegetation preferentially colonized steeper slopes (mean 43.20°) that offer structural refuge from active lahar flows, whereas flatter depositional beds (mean 23.64°) remained largely barren. Conversely, elevation ( 798 masl) showed no significant correlation (p = 0.68), indicating that secondary fluvial disturbances override broad altitudinal gradients within this active corridor. This study demonstrates a validated, reproducible UAV framework for high-precision ecological monitoring, providing fundamental insights for targeted post-eruption restoration strategies.